Possibilities of using of the venture capital as an innovative instrument in conditions of the Slovak republic in the competence of the National Agency for Development Small and Medium Enterprises - Mária Szabóová (Polityki Europejskie, Finanse i Marketing)
The contribution describes the venture capital as an innovative instrument used in the Slovak republic. Basic characteristic of venture capital presents its advantages and disadvantages, as well as describes the existing venture capital funds in the Slovak republic and the venture capital programmes are given in the first part. Hereby, the contribution describes monitoring of development of venture capital investments in the Slovak republic in the competence of the National Agency for Development Small and Medium Enterprises. Finally, the paper presents possibilities as we can improve availability of the venture capital in our conditions